THE RELATIONSHIP BETWEEN KEGEL EXERCISES WITH PERINUEM WOUND HEALING IN POST PARTUM WOMEN AT CATUBOUW HEALTH CENTER, CATUBOUW DISTRICT, PEGUNUNGAN ARFAK DISTRICT - Wiselmina Parantean; Siti Ni’amah; Suwi’I (LPPM AN NUUR, 2023)
Background: High risk/complication is a state of deviation from normal, which directly causes morbidity and death for both mother and baby.Purpose: Research Objectives: to determine the relationship between Kegel exercises and perineal wound healing in post partum mothers at the Catubouw Health Center, Catubouw District, Arfak Mountains DistrictMethod: The type of research used is descriptive analytic with a cross sectional approach. The population is post partum mothers. The sampling technique used is total sampling. The sample in this study were 30 post partum mothersResults: Some of the respondents who did not do Kegel exercises on post partum mothers were 15 people (50%), did Kegel exercises on post partum mothers by 15 people (50%), Most of the respondents experienced slow healing of perineal wounds as many as 16 people (53 .3%), there is a relationship between Kegel exercises and perineal wound healing in post partum mothers (Chi-Square count obtained 8.051 and p value = 0.003).Conclusion: It is recommended that health centers through nurse and midwife health workers be able to provide information and Kegel exercise training for every pregnant woman and postpartum mother in her working area